Konsep Integrasi Ilmu dalam Pandangan Ismail Raji Al-Faruqi - Arifuddin, Arifuddin (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
The development of science grows rapidly. However, this phenomenon raises a huge impact for Muslims. It has been our behavior that distinguish between Moslem Science and other knowledge. There is a discriminative treatment against the two types of science. Muslims are divided into those who have positive perception of the Islamic sciences, and negative to other, or vice versa. Based on the reality, Al-Faruqi says that there is no other way to raise Islam, except to reassess the culture of Islamic scholarship in the past, present and modern scholarship as well, and then process them into scientific to be a mercy to the world through what called